The Indonesian Government's Efforts to Improve Health Services and Facilities in Rural Areas Related to Health Laws - Imam Muhaji (Journal La Sociale, 2021)
Indonesian citizens must have the ability to access appropriate health care and facilities. Rural regions, on the other hand, suffer from a lack of resources and infrastructure owing to a variety of reasons. This village's health situation is clearly not in compliance with the existing health regulations. As a result, scholars are involved in examining federal efforts linked to health legislation to enhance health care and infrastructure in remote communities. This paper employs the secondary data approach as well as literature analysis. According to the findings, certain regions do not have enough health care and infrastructure. The government has made efforts to develop these health services and facilities so far; nevertheless, these efforts are insufficient, and further effort is needed so that all rural communities will benefit from the outcomes.